THE ROLE OF SOCIETY IN THE DEVELOPMENT OF THE CREATIVE ECONOMY IN THE INDUSTRIAL AGE 4.0 - Siti Fatimah; Yanti Purwanti (SEAN Institute, 2023)
The Industrial Age 4.0 was marked by the adoption of digital technology which affected various aspects of life, including the economy. The creative economy is one of the sectors that is growing rapidly in this era, involving economic activities that focus on the production and distribution of creative products and services. The purpose of this research is to examine the role of society in the development of the creative economy in the era of Industry 4.0. This study employs a qualitative approach with a descriptive methodology and literature as its secondary data source. The findings of this study indicate that the fourth industrial revolution has had an impact on the development of the creative economy in Indonesia, particularly in terms of the use of information and communication technology (ICT) in digitally-based creative industries. However, its development is not immune to obstacles, such as market obstacles, knowledge and technology transfer obstacles, human resource obstacles, and bureaucratic obstacles. In order to develop the creative economy through innovation and creativity, collaboration and networking, consumers and customers, and ecosystem growth, community participation is required. By illuminating the role of society in the development of the creative economy, the findings of this study can aid the government, institutions, and pertinent stakeholders in the design of policies that foster the expansion of the creative economy sector. In addition, this research can shed light on the significance of the community's role in establishing an innovative and sustainable economy in the era of Industry 4.0.